Strobilurin and boscalid in the quality of net melon fruits - Macedo, Ana Claudia [UNESP]; Amaro, Amanda Cristina Esteves [UNESP]; Ramos, Anamaria Ribeiro Pereira [UNESP]; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (Universidade Estadual de Londrina, 2017)
Until recently, fungicides were used exclusively for disease control; however observations of physiological effects brought a new concept to the use of these products. Strobilurins have positive physiological effects on crop yield, due to the increase of liquid photosynthesis and better hormonal balance. However, boscalid complements the action of these fungicides, applied alternately or together. The aim of this study was to evaluate the effect of strobilurins (azoxystrobin and pyraclostrobin), boscalid and the mixture of these on the physical-chemical quality of net melon fruits (Cucumis melo var. Reticulatus). The experiment was conducted in the municipality of São Manuel (SP), using the hybrid of Cantaloupe M2-308 net melon, the experimental design was in randomized blocks with five replicates. The treatments used were: T1 - control; T2 - azoxystrobin 60g ha-1 of active principle (a.p.); T3 - boscalid 75g ha-1 of the a.p.; T4 - pyraclostrobin 50g ha-1 of the a.p.; T5 - boscalid (37,5g ha-1) of the a.p. + pyraclostrobin (25g ha-1) of the a.p. The first application of the treatments was carried out at fourteen days after the transplanting of the seedlings and the others at seven day intervals, totaling eight applications throughout the cycle. Two fruits of each plot were collected, which were identified for analysis in the laboratory. The following characteristics were evaluated: fresh fruit mass; mesocarp thickness, pulp texture, peel trajectory, pH, titratable acidity, soluble solids and the ratio. The results were submitted to analysis of variance and the averages compared by the Tukey test at 5% probability using the SISVAR program. The fruits of the plants treated with boscalid 75g ha-1 were the ones that showed higher concentration of soluble solids and low titratable acidity, resulting in a better ratio. Despite the lower value, the fruits of the plants treated with pyraclostrobin 50g ha-1 showed a high ratio value, besides presenting higher value for pulp texture. The mixture of boscalid (37.5g ha-1) + pyraclostrobin (25g ha-1) also showed high values of soluble solids which resulted in a good ratio value.
Keywords: Ratio; Cucumis melo var; Post-harvest; Reticulatus; Soluble solids